Perioperative dexmedetomidine and 5-year survival in patients undergoing cardiac surgery. (August 2021) - Peng, Ke; Shen, Yue-ping; Ying, Yao-yu; Kiaii, Bob; Rodriguez, Victor; Boyd, Douglas; Applegate, Richard L.; Lubarsky, David A.; Zhang, Zugui; Xia, Zhengyuan; Feng, Xiao-mei; Yang, Jian-ping; et al.
Abstract: Background: Dexmedetomidine sedation has been associated with favourable outcomes after surgery. We aimed to assess whether perioperative dexmedetomidine use is associated with improved survival after cardiac surgery. Methods: This retrospective cohort study included 2068 patients undergoing on-pump coronary artery bypass grafting and/or valve surgery. Among them, 1029 patients received dexmedetomidine, and 1039 patients did not. Intravenous dexmedetomidine infusion of 0.007 μg kg −1 min −1 was initiated before or immediately after cardiopulmonary bypass and lasted for < 24 h. The primary outcome was 5-year survival after cardiac surgery. The propensity scores matching (PSM), inverse probability of treatment weighting (IPTW), and overlap weighting approaches were used to minimise bias. Survival analyses were performed with Cox proportional-hazard models. Results: The median age was 63 yr old and the male to female ratio was 71:29 in both groups. Baseline covariates were balanced between groups after adjustment using PSM, IPTW, or overlap weighting. Patients receiving dexmedetomidine in cardiac surgical procedures had higher survival during postoperative 5 yr in unadjusted analysis (hazard ratio [HR]=0.63; 95% confidence interval [CI], 0.51–0.78; P <0.001), and after adjustment with PSM (HR=0.63; 95% CI, 0.45–0.89; P =0.009), IPTW (HR=0.70; 95% CI, 0.51–0.95; P =0.023), or overlap weighting (HR=0.67; 95% CI, 0.51–0.89; P =0.006). The 5-yr mortality rate after cardiac surgery was 13% and 20% in the dexmedetomidine and non-dexmedetomidine groups, respectively (PSM adjusted odds ratio=0.61; 95% CI, 0.42–0.89; P =0.010). Conclusion: Perioperative dexmedetomidine infusion was associated with improved 5-yr survival in patients undergoing cardiac surgery.